Frequency and factors associated with focused antenatal care in Guinea: Analysis of the DHS 2018 - Maimouna Baldé; Jean B.D. Loua; Tiany Sidibé; Fanta Barry; Bienvenu S. Camara; Ramata Diallo; Madeleine Toure; Kaba S. Keita; Sadan Camara; Mamadou D. Balde (AOSIS, 2024)
Background: In Guinea, despite women's recourse to antenatal care (ANC), little remains known about the use of focused antenatal care (FANC), contained in the ANC package. Aim: The aim of this study was to analyse the frequency and factors associated with FANC, using data from the Demographic and Health Survey (DHS) 2018. Setting: This study was conducted in Guinea. Methods: This was a secondary analysis of data from the DHS conducted in 2018 in Guinea. It included all women who achieved at least one ANC visit in the last 2 years prior to the survey. Multivariate logistic regression was received to identify factors associated with FANC. Stata 16 software was used for the analysis. Results: This study shows that in Guinea, between 2016 and 2018 only 33% of women undergoing ANC received a FANC. The most commonly used service was blood pressure measurement (93%), while the least commonly used service was deworming (42%). Factors associated with FANC were living in the Kindia region (odds ratio = 1.7; 95% confidence interval: 1.04-2.97); not intending to become pregnant for this pregnancy; belonging to a poor household; and having made 3, 4 or more ANC visits. Conclusion: This study reports a low proportion of women receiving the full package of ANC. Contribution: In order to improve this indicator, greater efforts need to be made in certain regions of the country to target pregnant women who achieve fewer ANC visits, carry pregnancies that were not intentional or belong to poorer households.